Industri Pariwisata dan Mobilitas Pekerjaan Perempuan di Kawasan Ekonomi Khusus (KEK) Mandalika Kuta Lombok - Syafruddin Syafruddin; Hairil Wadi; Suud Suud (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
This study aims to understand and map the tourism industry and women’s employment mobility in the Special Economic Zone (SEZ) of Mandalika Kuta Lombok, West Nusa Tenggara, Indonesia. This study was a qualitative study using a case study approach with a group analysis unit. Data were obtained through observation, interviews, and documentation. The informants are an optional or criterion-based selection. Informants in this study were 120 informants. Informants were selected using a purposive sampling technique. The informants in this study are not to represent the population but represent information. Data analysis was processed through three stages. The results of the study found that the tourism industry in the Special Economic Zone of Mandalika Kuta Lombok has encouraged the new job creation and job types that were previously unknown by the community. In the category of self-employment and wage employment, there is an increase in the number due to a decrease in the status of casual work. This is a sign that there are significant job changes and job mobility. This is caused by low wages, inconvenience at work, and family factors. With the creation of various types of new jobs and the pattern of employment mobility, the efforts of self-improvement are needed, especially in terms of education and skills. Provincial and District Governments need to conduct a study of the potential and employment opportunities needed for women in the tourism industry to create links and matches between various employment sectors in the tourism industry.